Similarities between Ashi acupoints and myofascial trigger points: Exploring the relationship between body surface treatment points - Lee, Seoyoung; Lee, In-Seon; Chae, Younbyoung (Frontiers in Neuroscience, 2022)
Although acupuncture points and myofascial trigger points (TPs) are based in different medical fields, the two points share important attributes. We explored the relationship between acupuncture points and TPs based on their characteristics and the results of previous studies. We outlined the relationship between acupuncture points and TPs by examining their similarities and differences. Among the acupuncture point subgroups, TPs mostly corresponded to Ashi points. Based on the common features of TPs and Ashi points, we suggest that TPs are more closely related to Ashi points than to other acupoints. However, TPs also share some features, such as pain indication and location, with classical acupuncture points (CA) and extra acupuncture points (EA), which makes it difficult to elucidate their relationship with other subgroups. Therefore, we suggest to understand the relationship of CAs, EAs, Ashi points, and TPs. In this report, we concluded that concerning muscular pain symptoms Ashi points and TPs are indistinguishable.